Efektivitas Pelayanan Loka Pom Tanjungpinang dalam Membantu Konsumen Memilih Kosmetik yang Aman Melalui Aplikasi BPOM Mobile - Dewi Zefanya Siahaan; Fitri Kurnianingsih; Ramadhani Setiawan (Jurnal Relasi Publik, 2023)
This research refers to the decision of presidential regulation number 80 of 2017 concerning the Food and Drug Supervisory Agency and based on the approval letter of the Minister of Administrative Reform and Bureaucratic Reform Number B/411/M.KT.01 2018 dated June 8, 2018 concerning the Arrangement of Technical Implementation Units of the Food and Drug Supervisory Agency. /In this study, the problem for researchers is to find out how the socialization of the POM Workshop in Tanjungpinang is to help the consumer community to choose products that already have a distribution permit in order to protect consumers from dangerous cosmetics by introducing the Bpom Mobile application as a very useful application to help the public in purchasing cosmetics that are safe and have a distribution permit. the research used in this research is to use a descriptive qualitative approach with primary and secondary data sources and use data collection techniques by observation, interview, and documentation. The theory in this study refers to Budiani's theory (2007: 53), namely the accuracy of program targets, program socialization, program objectives, program monitoring. The results showed that the first indicator, namely the accuracy of program targets, still had to set age limits to be able to use the Bpom Mobile application so that people could find out the rules for using the Bpom Mobile application. The second indicator is the socialization of the program, the Pom Workshop in Tanjungpinang makes a lot of socialization both for the community, students of school children who make Bpom Mobile material an important material in every socialization / counseling and even open a stand to explain the Bpom Mobile application. The third indicator is the purpose of the program, has the aim that the public knows that there is an application that is very helpful for buying a product to ascertain whether the product used has a distribution permit and is safe for use in everyday life. The fourth indicator is monitoring program results, the POM Workshop in Tanjungpinang sees that the results of the Bpom Mobile application program are beneficial to the community even though it is difficult for people who cannot use cellphones to use the Bpom Mobile application. The conclusion of this study is that the socialization of Bpom has not been effective because there are still many people who do not know that the Bpom Mobile application exists.